Use of response surface methodology in the development of guava concentrate - Yusof, Salmah; Talib, Zaharah; Mohamed, Suhaila; Bakar, Abdullah Abu (Wiley, 1988)
A response surface methodology (RSM) was used for the determination of optimum pH, processing temperature and ºBrix to produce an acceptable guava concentrate. These three factors were used as independent variables whose effects on colour and viscosity of the concentrate, as well as on titratable acidity, body (mouthfeel), flavour and overall acceptability of the reconstituted juice were evaluated. The R2 values for colour, titratable acidity and overall acceptability were greater than 0·9. Analysis of the regression coefficients showed that the pH of the concentrate was the most important factor affecting the characteristics of the product as it exerted a highly significant influence on the colour of the concentrate as well as on titratable acidity, flavour and overall acceptability of the juice. The colour, titratable acidity and overall acceptability were affected by ºBrix whereas temperature influenced only the colour of the product. The combinations required to achieve suitable colour were pH 2·4–2·9, 75–81°C and 48–55°Brix, orpH 4·0, 87–95°C and 46°Brix. For acceptable flavour, pH 3·3–3·6, 78–86°C and 50·9°Brix are required, and for maximum overall acceptability, pH 3·3–3·9, 79·l°C and 35–55°Brix.